O-036 Venous sinus stenosis balloon angioplasty for idiopathic intracranial hypertension. (23rd July 2022) - Martinez Gutierrez, J; Kole, M; Lopez-Rivera, V; Inam, M; Tang, R; Al-Zubidi, N; Al-Zubidi, N; Adesina, O; Lekka, E; Engstrom, A; Sheth, S; Pedroza, C; et al.
Abstract : Background: Patients with Idiopathic Intracranial Hypertension (IIH) frequently harbor concurrent venous sinus stenosis (VSS). Venous stenting to support outflow and CSF clearance has emerged as an effective treatment. However, the use of prolonged aggressive antiplatelet regimens and risk of stent-related thrombosis or stenosis can limit its use. We investigated the utility and safety of primary VSS balloon angioplasty in patients with IIH. Methods: We queried a prospectively maintained registry of endovascular interventions in IIH patients. Consecutive cases of VSS angioplasty (Group A) were compared to consecutive cases of stenting (Group S). Inclusion criteria included patients with confirmed IIH and angiographically proven VSS. Bivariate statistical analyses were performed. Results: 62 patients met the inclusion criteria for the study. Median age was 33 [IQR 26–37], 74% females with mean BMI of 35±7 kg/m2. Baseline characteristics between the Group A (9/62) and Groups S (53/62) were similar ( table 1 ). Group S had higher rate of improvement in papilledema at 6 weeks and 6 months (44 vs 93%, p=0.002 and 44 vs 92%, p=0.004) as well as all subjective symptoms ( table 2 ). Group S had greater improvement in post-intervention venous pressure gradient (8 vs 3 mmHg, p=0.02) and 6 month opening pressure (23 vs 36 cmH2O, p<0.001). Treatment failure leading to shunt rescue was greater in Group A (44 vs 2%, p=0.001). A single complication of a subdural hematoma was observed in Group A. Conclusion: Primary balloon angioplasty offered limited and transient improvement in IIH symptoms with a high failure rate. These findings suggest a limited role of VSS balloon angioplasty as a temporary rescue in refractory IIH patients not amenable to stenting or shunting. Data analyzed by Students' t-test for continuous variables, or Fisher's exact for categorical variables. For symptom improvement data, analysis was performed comparing symptom improvement in patients undergoing angioplasty alone versus stenting at two different time points, and p-value is reported for comparison of the two treatment groups at both time points. Disclosures: J. Martinez Gutierrez: None. M. Kole: None. V. Lopez-Rivera: None. M. Inam: None. R. Tang: None. N. Al-Zubidi: None. N. Al-Zubidi: None. O. Adesina: None. E. Lekka: None. A. Engstrom: None. S. Sheth: None. C. Pedroza: None. A. Day: None. P. Chen: 1; C; Weatherhead Foundation.